Twentieth year of the Journal of Vegetation Science: the journal for all vegetation scientists - Wilson, J. Bastow (2009)
The Journal of Vegetation Science was launched by the International Association for Vegetation Science (IAVS) in 1990, specifically to be a journal owned and governed by the Association. Now, in its 20th year of publication, it is the reference journal for plant community ecology. Eddy van der Maarel concluded in his editorial of the first issue: ‘‘Vegetation science is rapidly developing towards a general science of plant communities with its own body of theory and an enormous potential for application in the fields of nature conservation and environmental management. . . . Let the Journal of Vegetation Science be a journal for all vegetation scientists’’ (van der Maarel 1990). The world has changed much in those 19 years. So has vegetation science, with the Journal of Vegetation Science drawing together vegetation scientists from almost all the countries of the world and with every approach to the subject. Peter White had been with the Journal of Vegetation Science since it started. He had been an Associate Editor since they existed, and a Chief Editor since they did. He is now taking a break1 from the Journal, primarily because he is overseeing developments in the North Carolina Botanic Garden. This is a good time to thank him for all his work and all his wisdom since 1990.